2003
DOI: 10.1128/aem.69.5.2773-2785.2003
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Vibrio cholerae in Chesapeake Bay

Abstract: Vibrio cholerae is autochthonous to natural waters and can pose a health risk when it is consumed via untreated water or contaminated shellfish. The correlation between the occurrence of V. cholerae in Chesapeake Bay and environmental factors was investigated over a 3-year period. Water and plankton samples were collected monthly from five shore sampling sites in northern Chesapeake Bay (January 1998 to February 2000) and from research cruise stations on a north-south transect (summers of 1999 and 2000). Enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
165
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(198 citation statements)
references
References 66 publications
24
165
1
8
Order By: Relevance
“…It was argued that a shift of the average environmental temperature towards the range optimal for growth for pathogens, which is typically around 37 u C, would enable pathogenic bacteria to compete better for nutrients with the low temperature-adapted indigenous heterotrophic microbial flora. Supporting this hypothesis is that temperature is frequently reported to influence growth and occurrence of V. cholerae O1 in natural waters with low salinity (Huq et al, 2005;Louis et al, 2003). Also, the faecal indicator bacterium E. coli was reported to grow outside its host in tropical waters, but not at higher latitudes in the northern hemisphere, where the average annual water temperature is lower (Winfield & Groisman, 2003).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…It was argued that a shift of the average environmental temperature towards the range optimal for growth for pathogens, which is typically around 37 u C, would enable pathogenic bacteria to compete better for nutrients with the low temperature-adapted indigenous heterotrophic microbial flora. Supporting this hypothesis is that temperature is frequently reported to influence growth and occurrence of V. cholerae O1 in natural waters with low salinity (Huq et al, 2005;Louis et al, 2003). Also, the faecal indicator bacterium E. coli was reported to grow outside its host in tropical waters, but not at higher latitudes in the northern hemisphere, where the average annual water temperature is lower (Winfield & Groisman, 2003).…”
Section: Discussionsupporting
confidence: 51%
“…Earlier reports, based on the distribution of V. cholerae in estuarine water, had already indicated the preference of this pathogen for moderate salinity with respect to optimum conditions for growth (Huq et al, 2005;Louis et al, 2003;Miller et al, 1982). Also, microcosm studies, using artificial seawater and tryptone as a carbon source, had previously shown that V. cholerae exhibits highest specific growth rates at moderate salinity (Singleton et al, 1982a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, contrary to the competitive dominance observed in Euprymna, Vibrio symbionts in Sepiola are host generalists [16]. Other studies with bivalve and vertebrate hosts have also demonstrated that salinity and temperature influence host colonization [19][20][21][22], abundance and distribution [23][24][25], physiological state and survival [26][27][28], and the adhesive capabilities to host epithelia [29]. Hence, previous research has made it apparent that salinity and temperature influence all life cycle stages of Vibrio species, including the biogeography of free-living cells, host attachment with subsequent proliferation during symbiosis, and the alternative evolutionary trajectories available to different host ranges.…”
Section: Introductionmentioning
confidence: 99%